2017
DOI: 10.3348/kjr.2017.18.1.6
|View full text |Cite
|
Sign up to set email alerts
|

Evolving Cancer Classification in the Era of Personalized Medicine: A Primer for Radiologists

Abstract: Traditionally tumors were classified based on anatomic location but now specific genetic mutations in cancers are leading to treatment of tumors with molecular targeted therapies. This has led to a paradigm shift in the classification and treatment of cancer. Tumors treated with molecular targeted therapies often show morphological changes rather than change in size and are associated with class specific and drug specific toxicities, different from those encountered with conventional chemotherapeutic agents. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…Yet, a molecular definition of AT signatures that defines metabolically-unhealthy obese sub-phenotype(s) has not been systematically attempted. In oncology, molecular typing of tumors largely relies on the identification of different tumors' genetic perturbations, increasingly used to guide patients' management [51] . Genetic polymorphisms related to obesity sub-phenotypes and/or responses to therapy are just beginning to be unraveled [52] .…”
Section: Discussionmentioning
confidence: 99%
“…Yet, a molecular definition of AT signatures that defines metabolically-unhealthy obese sub-phenotype(s) has not been systematically attempted. In oncology, molecular typing of tumors largely relies on the identification of different tumors' genetic perturbations, increasingly used to guide patients' management [51] . Genetic polymorphisms related to obesity sub-phenotypes and/or responses to therapy are just beginning to be unraveled [52] .…”
Section: Discussionmentioning
confidence: 99%
“…Solid tumors are classified according to the type of cells forming the tumor, where localized solid tumors are either sarcoma, carcinoma, or lymphoma (1). Solid tumor cancers directly affect patient survival, particularly when tumors are malignant (2).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have addressed the clinico-pathologic characteristics of IMAs as an evolving disease entity. Particularly, in terms of genetic profile, IMA is correlated with the absence of epidermal growth factor receptor (EGFR) mutations and the presence of KRAS mutations, which indicates that these tumors are unlikely to respond to EGFR-tyrosine kinase inhibitors such as gefitinib and erlotinib (4512212223). Many reports have also shown that IMA is associated with lower rates of pleural involvement, lymphatic permeation, and vascular invasion, in contrast to frequent aerogenous spread (6781124).…”
Section: Discussionmentioning
confidence: 99%